Unification of Discount Rates Used in External Debt Analysis for Low-Income Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2013)
This paper proposes reforms to the discount rates used by the Bank and the Fund to (a) calculate the present value (PV) of the external debt of low-income countries (LICs) in debt sustainability analyses (DSAs) and (b) to calculate the grant element of individual loans. Consistent with the conclusions of the March 2013 review of the Fund's debt limits policy, the paper proposes a single uniform discount rate to be used for these related operational purposes. It has been prepared as a joint product of Bank and Fund staff, with the exception of the decision, which is Fund-specific.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet